2004
DOI: 10.1002/adem.200400092
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Carbon Nanotube Composite Fibers

Abstract: Carbon nanotubes have been the focus of considerable research over the last decade. Because of their remarkable structural, mechanical, electrical, and thermal properties, [1] diverse applications have been envisioned. [2] Realization of these property advantages has been frustrated by material heterogeneity and impurities: catalyst and/or impurity carbons are present and as-produced nanotubes are mixtures of moderate bandgap semiconductors, very small bandgap semiconductors, and metallic conductors. Also, sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
40
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 28 publications
1
40
0
Order By: Relevance
“…8,13,14 One of the most successful methods used to prepare SWNT-based composite fibers via wetspinning is to inject a surfactant stabilised SWNT dispersion into a bath that contains a polymer coagulant. [15][16][17][18][19][20][21] In this regard, a compromise in electrical conductivity, particularly for SWNTbased composite fibers that display excellent mechanical reinforcement, is observed. As an example, supertough PVA-SWNT fibers (prepared via the coagulation method), exhibit modulus, strength and toughness values as high as 80 GPa, 1.8 GPa and 570 J g À1 , respectively; 17 however, the electrical conductivity is low ($2.5 S cm À1 ) a direct result of the adverse effect of PVA (an insulator) on the overall electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,13,14 One of the most successful methods used to prepare SWNT-based composite fibers via wetspinning is to inject a surfactant stabilised SWNT dispersion into a bath that contains a polymer coagulant. [15][16][17][18][19][20][21] In this regard, a compromise in electrical conductivity, particularly for SWNTbased composite fibers that display excellent mechanical reinforcement, is observed. As an example, supertough PVA-SWNT fibers (prepared via the coagulation method), exhibit modulus, strength and toughness values as high as 80 GPa, 1.8 GPa and 570 J g À1 , respectively; 17 however, the electrical conductivity is low ($2.5 S cm À1 ) a direct result of the adverse effect of PVA (an insulator) on the overall electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…17,19 Although the removal of PVA via thermal annealing can enhance the electrical conductivity, the mechanical properties are severely compromised. 18,19 However, it has been shown that when the polymer host is inherently conducting such as polyaniline and polypyrrole, the addition of SWNT during the fiber spinning process provides significant benefits including, but not limited to, high electrical conductivity in contrast with an insulator polymer host such as PVA. [22][23][24][25] In a mechanically reinforced system, enhancement is generally achieved at low CNT loadings (typically 1 to 10% of SWNT).…”
Section: Introductionmentioning
confidence: 99%
“…While quite high actuation stresses were obtained in these thermally annealed CNT fibers, their low flexibility and high creep during charge and discharge were noted as significant problems. [5] Similarly, fibers spun without the aid of a polymer binder [1] produce high conductivities (140 S cm -1 after thermal annealing) and capacitances…”
mentioning
confidence: 99%
“…Additionally, these SWNT fibers have been successfully utilized in the fabrication of electrochemical devices, such as electromechanical actuators [1,12] and supercapacitors. [10,11] However, unless the polymer is removed by pyrolysis (which degrades the mechanical properties of the fiber), performance of these electrochemical devices is limited by the low electrical conductivity of the nanotube/polymer composite fibers and degradation of mechanical stability when the PVA in these fibers is converted into an ionic conductor.…”
mentioning
confidence: 99%